Mechanisms underlying immune tolerance caused by recombinant Echinococcus granulosus antigens Eg mMDH and Eg10 in dendritic cells - Wang, Yana (PLoS One, 2018)
Mice immunized with recombinant Echinococcus granulosus antigens Eg10 and Eg mMDH do not show elevated resistance to E. granulosus infection but show aggravated infection instead. To gain a deeper insight in the immune tolerance mechanisms in mice immunized with Eg10 and Eg mMDH, this study simulated the immune tolerance process in vitro by culturing bone marrow-derived dendritic cells (BMDCs) in the presence of Eg10 or Eg mMDH. Scanning electron microscopy revealed that Eg10- and Eg mMDH-treated DCs exhibited immature cell morphology, while addition of LPS to the cells induced changes in cell morphology and an increase in the number of cell-surface protrusions. This observation was consistent with the increased expression of the cell-surface molecules MHCII and CD80 in Eg10- and Eg mMDH-treated DCs pretreated with LPS. DCs exposed to the two antigens had a very weak ability to induce T-cell proliferation, but could promote the formation of Treg cells. Introduction of the indoleamine 2,3-dioxygenase (IDO) inhibitor, 1-methyl tryptopha (1-MT) enhanced the ability of the antigens to induce T cells and inhibited the induction of Treg cells. Eg mMDH-treated DCs showed a strong response to 1-MT: the DCs had high mRNA levels of IDO, IL-6, and IL-10, while 1-MT decreased the expression. In contrast, DCs treated with Eg10 did not show significant changes after 1-MT treatment. Eg mMDH inhibited DC maturation and promoted IDO expression, which, on the one hand, decreased the ability of DCs to induce T-cell proliferation, resulting in T-cell anergy, and on the other hand, induced the formation of Tregs, resulting in an immunosuppressive effect. In contrast, the escape mechanisms induced by Eg10 did not primarily depend on the IDO pathway and might involve other mechanisms that need to be further explored.